Imminent Immanence of Judeo-Evangelical Nationalism: American Christian Zionists and Israel as the Future Redeemer Nation and State (Relegere: Studies in Religion and Reception, 2012)
For tens of millions of American evangelical Christians, the eschatology of God's plan for a Chosen People and a Chosen land-scape is essential to explaining the contemporary relationship. Time and space here merge as prophetic time manifests itself in prophetic space. Judeo-Christian nationalism lies not in America as the redeemer state, but rather in Israel as future prophetic time becomes immanent as "signs" of an imminent apocalypse are imagined to take place. The hyphenation of Judeo-Christian is key to developing a future, dualist memory territorially dividing what is "ours" and "theirs" in simplistic geopolitical divisions drawn up between Jews and Christians on the one hand, and everybody else (especially Muslims) on the other.